2008
DOI: 10.1186/1471-2105-9-263
|View full text |Cite
|
Sign up to set email alerts
|

GPR17: Molecular modeling and dynamics studies of the 3-D structure and purinergic ligand binding features in comparison with P2Y receptors

Abstract: Background: GPR17 is a G-protein-coupled receptor located at intermediate phylogenetic position between two distinct receptor families: the P2Y and CysLT receptors for extracellular nucleotides and cysteinyl-LTs, respectively. We previously showed that GPR17 can indeed respond to both classes of endogenous ligands and to synthetic compounds active at the above receptor families, thus representing the first fully characterized non-peptide "hybrid" GPCR. In a rat brain focal ischemia model, the selective in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 54 publications
1
75
1
Order By: Relevance
“…Although multiple follow-up studies consistent with this original report have been published by the same group (Parravicini et al, 2008;Pugliese et al, 2009;Buccioni et al, 2011;Daniele et al, 2011;Coppi et al, 2013), Benned-Jensen and Rosenkilde (2010) reported that UDP and UDP-glucose, but not cysteinyl leukotrienes, promoted GPR17-dependent guanosine 59-O-(3-[…”
Section: Introductionmentioning
confidence: 51%
“…Although multiple follow-up studies consistent with this original report have been published by the same group (Parravicini et al, 2008;Pugliese et al, 2009;Buccioni et al, 2011;Daniele et al, 2011;Coppi et al, 2013), Benned-Jensen and Rosenkilde (2010) reported that UDP and UDP-glucose, but not cysteinyl leukotrienes, promoted GPR17-dependent guanosine 59-O-(3-[…”
Section: Introductionmentioning
confidence: 51%
“…To verify if two distinct binding sites (one for nucleotides and the other for cysLTs) were present on GPR17 (Parravicini et al, 2008, the effects of the CysLT antagonist (montelukast) and the purinergic antagonist (cangrelor) were tested on the LTD 4 -and UDP-glucose-induced responses, respectively. Montelukast inhibited LTD 4 -mediated responses with an IC 50 value of 23.0 Ϯ 1.4 nM that was comparable with that from previous studies (Ciana et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…One group has confirmed independently that GPR17 responds to purinergic uracil ligands (Benned-Jensen and Rosenkilde, 2010), whereas Maekawa et al (2009) have suggested GPR17 as a constitutive, negative regulator for CysLT 1 . Bioinformatic data have suggested the presence of two distinct binding sites on GPR17, one for nucleotides and the other for cysLT (Parravicini et al, 2008; however, it is still unclear if GPR17 predominantly behaves as a purinergic receptor that may be able to modulate responses to cysLTs through a protein-protein interaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has led to the "deorphanization" of the G protein-coupled receptor (GPCR) 5 referred to as GPR17, which is located at an intermediate phylogenetic position between the purinergic P2Y receptors and the CysLT 1 and CysLT 2 receptors for cysteinyl-leukotrienes (cysLTs; [1][2][3][4][5][6]. Both recombinant and native GPR17 receptors respond to uracil nucleotides (e.g.…”
mentioning
confidence: 99%